Selection of Tree Species for Energy Plantation in Arid - Semi-arid Area - III. Comparative Growth Studies - Thaker, Vrinda S.; Singh, Yash Dev (Indian Forester, 2001)
Comparative growth analysis of three tree species viz. Acacia nilotica, Leucaena leucocephala and Prosopis juliflora were studied. The correlation coefficient and regression models were worked out between biomass and dependable variables like, stem weight, diameter at base, leaf weight, branch weight and plant height. Amongst the three species tested, L. leucocephala recorded maximum biomass followed by A. nilotica and P. juliflora.